KELUARGA BERENCANA DI MASA PANDEMI DITINJAU DARI HUKUM ISLAM - Chaula Luthfia (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2021)
The family planning program established by the Indonesian Family Planning Association (PKBI) since 1957 with its services, namely managing or managing pregnancies, treating infertility, and offering marriage counseling for married couples. In its development in the New Order Era, the family planning program was used as a solution to population problems in Indonesia. This family planning aims to regulate childbirth, regulate distance, the ideal age of childbirth, and regulate pregnancy through programs, protection and assistance in accordance with reproductive rights. Islam does not contain rules about family planning but in Islam it is known to exist azl. Here it is important to see how Islam views family planning law. During the Covid-19 pandemic, the government imposed new habits to prevent the transmission of Covid-19. One of them is the family planning program, where mothers give birth during Covid-19 have a higher risk of contracting it. Pregnant women have weaker immunity than non-pregnant women. Here it is important to see how Islam views family planning law during the Covid-19 pandemic. This research is a library research with a normative approach. With primary sources Presidential Decree Number 32 of 1969 concerning the Implementation of the Family Planning Program. The result of this study is a family planning program that aims to create a peaceful, prosperous family, not contrary to Islamic law. Where to protect the health of mothers and children and raise children who are morally straight, smart, and healthy, family planning programs are a solution. Moreover, the recommendation of the family planning program during the Covid-19 pandemic, where to protect the health of mothers and children, the family planning program is the right solution during the Covid-19 pandemic. But family planning is prohibited from using it if it has a terrible social impact and is done with bad intentions